Teaching Gender Research Methods for Leadership: Reflections from Rwanda - Dantas, Jaya A R (UTS epress, 2021)
This chapter discusses teaching and research undertaken by the author in Rwanda between 1997 and 2011. The author draws on her experiences of establishing and running an institution in Rwanda from 1997 to 1999, undertaking research for her PhD in 2000, visiting the country in 2007 to gain further insights into the reconstruction of education and in 2011 teaching at the Centre for Gender, Culture and Development. Using a gender lens, the author reflects on teaching gender research methods, the interactions with an amazing first cohort of students and the immense leadership potential shown by the students. The chapter concludes with some recommendations and implications.